The Ottawa Panel guidelines on programmes involving therapeutic exercise for the management of hand osteoarthritis†. (November 2018) - Brosseau, Lucie; Thevenot, Odette; MacKiddie, Olivia; Taki, Jade; Wells, George A; Guitard, Paulette; Léonard, Guillaume; Paquet, Nicole; Aydin, Sibel Z; Toupin-April, Karine; Cavallo, Sabrina; Moe, Rikke Helene; et al.
Objective: To identify programmes involving therapeutic exercise that are effective for the management of hand osteoarthritis and to provide stakeholders with updated, moderate to high-quality recommendations supporting exercises for hand osteoarthritis. Methods: A systematic search and adapted selection criteria included comparable trials with exercise programmes for managing hand osteoarthritis. Based on the evaluated evidence, a panel of experts reached consensus through a Delphi approach endorsing the recommendations. A hierarchical alphabetical grading system (A, B, C+, C, C-, D-, D, D+, E, F) was based on clinical importance (≥15%) and statistical significance ( P  < 0.05). Results: Ten moderate- to high-quality studies were included. Eight studies with programmes involving therapeutic exercise (e.g. range of motion (ROM) + isotonic + isometric + functional exercise) seemed to be effective. Forty-six positive grade recommendations (i.e. A, B, C+) were obtained during short-term (<12 weeks) trials for pain, stiffness, physical function, grip strength, pinch strength, range of motion, global assessment, pressure pain threshold, fatigue and abductor pollicis longus moment and during long-term (>12 weeks) trials for physical function and pinch strength. Conclusion: Despite that many programmes involving exercise with positive recommendations for clinical outcomes are available to healthcare professionals and hand osteoarthritis patients that aid in the management of hand osteoarthritis, there is a need for further research to isolate the specific effect of exercise components.